Rapid reviews in health policy: a study of intended use in the New South Wales' Evidence Check programme. (18th November 2016) - Moore, Gabriel Mary; Redman, Sally; Turner, Tari; Haines, Mary
Abstract : Rapid reviews of research are a key way in which policy makers use research. This paper examines 74 rapid reviews commissioned by health policy agencies through the Sax Institute's Evidence Check programme. We examine what prompted policy makers to commission rapid reviews, their purpose, how and when they intended to use them, and how this varied by agency. Policy makers commissioned rapid reviews primarily as part of planned policy processes and to identify alternative solutions to problems. Government departments responsible for multiple policy domains were more likely to commission rapid reviews for agenda setting and to test new ideas.